2005
DOI: 10.1002/adsc.200404351
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Selectivity in Terpene Chemistry: Selective Hydrogenation versus Cascade Reactions over Copper Catalysts

Abstract: The selectivity of Cu/Al 2 O 3 under very mild catalytic hydrogenation conditions can be tuned only by switching the solvent. Geraniol can be converted in a one-pot one-step process into a mixture of citronellol and menthol in hydrocarbon solvents or reduced to citronellol with 98% selectivity in 2-propanol without any additive. Both reactions can be applied to essential oils or synthetic mixtures containing geraniol, citronellal and nerol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…On the contrary, allylic alcohols react very fast, much faster than their saturated analogues, as shown by the comparison between mirtenol and mirtanol (entry 18 versus 19) and of carveol and dihydrocarveol (entry 16 versus 17) although in this last case steric effects may also play a role. Selectivity is not high when secondary reactions can take place, as in the case of geraniol, which under these conditions gives citronellol and isopulegol,28 but anaerobic conditions avoid formation of the corresponding carboxylic acid which are often observed when using gold catalysts 12a. 29…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, allylic alcohols react very fast, much faster than their saturated analogues, as shown by the comparison between mirtenol and mirtanol (entry 18 versus 19) and of carveol and dihydrocarveol (entry 16 versus 17) although in this last case steric effects may also play a role. Selectivity is not high when secondary reactions can take place, as in the case of geraniol, which under these conditions gives citronellol and isopulegol,28 but anaerobic conditions avoid formation of the corresponding carboxylic acid which are often observed when using gold catalysts 12a. 29…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that the size of the metallic particles catalysts prepared by the chemisorption hydrolysis technique does not change very much going from 5 to 8% loading, 23b whereas the hydrogenation activity increases according to the higher Cu content. 28 On the other hand, the catalyst obtained using a zeolite support gave a messy product distribution where the desired product was present in a low amount.…”
Section: Communicationmentioning
confidence: 99%
“…Recently was reported (Scheme 8) [18]. It was demonstrated how the selectivity of the reaction with respect to citronellol and menthol could be switched based on the basicity of the solvent used, which is due to the complex reaction mechanism in the liquid phase.…”
Section: Methodsmentioning
confidence: 99%